2006
DOI: 10.1158/0008-5472.can-05-3388
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1 Genotype and Breast Cancer: Functional Studies and Epidemiologic Data Show Interactions between XRCC1 Codon 280 His and Smoking

Abstract: Tobacco smoke produces oxidative and alkylative DNA damage that necessitates repair by base excision repair coordinated by X-ray cross-complementing gene 1 (XRCC1). We investigated whether polymorphisms in XRCC1 alter DNA repair capacity and modify breast cancer risk associated with smoking. To show the functionality of the 280His variant, we evaluated single-strand break (SSB) repair capacity of isogenic Chinese hamster ovary cells expressing human forms of XRCC1 after exposure to hydrogen peroxide (H 2 O 2 )… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
53
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 38 publications
10
53
0
Order By: Relevance
“…The results show either a positive or null association between long-term smoking and N-acetyltransferase (NAT-2), CYP1A1, glutathione S-transferase, sulfotransferase 1A1 genes (Terry and Goodman, 2006). Studies of the BER enzyme, XRCC1, have shown a positive association of long-term smoking with breast cancer risk (Duell et al, 2001;Terry and Rohan, 2002;Patel et al, 2005;Pachkowski et al, 2006). Thus, mutations in the XRCC1 gene may influence the BER activity and reduce the repair of nonbulky DNA adducts generated by cigarette smoke constituents.…”
Section: Introductionmentioning
confidence: 99%
“…The results show either a positive or null association between long-term smoking and N-acetyltransferase (NAT-2), CYP1A1, glutathione S-transferase, sulfotransferase 1A1 genes (Terry and Goodman, 2006). Studies of the BER enzyme, XRCC1, have shown a positive association of long-term smoking with breast cancer risk (Duell et al, 2001;Terry and Rohan, 2002;Patel et al, 2005;Pachkowski et al, 2006). Thus, mutations in the XRCC1 gene may influence the BER activity and reduce the repair of nonbulky DNA adducts generated by cigarette smoke constituents.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Gln allele of the ERCC2 Lys751Gln SNP has been associated with both reduced NER capacity (Spitz et al 2001;Qiao et al 2002b) and increased prevalence of adducts (Palli et al 2001;Hou et al 2002;Tang et al 2002). Similar effects are seen in other repair systems, with variants of the BER proteins 8-oxoguanine DNA glycosylase 1 and X-ray cross-complementing group 1 showing reduced activity (Pachkowski et al 2006;Sokhansanj & Wilson, 2006). The same polymorphisms that appear to modulate repair capacity have been associated with cancer risk.…”
Section: Genetic Polymorphisms Dna Repair and Cancer Riskmentioning
confidence: 98%
“…Previous studies indicated that the XRCC1 399Gln allele is a BER gene polymorphism frequently inherited by American white women (allele frequency, 0.34-0.37) (14,15,20,21,(26)(27)(28)(29)40). Other ethnic groups have not been as well-studied.…”
Section: Ber Gene Polymorphisms In Breast Cancer: Xrcc1 399glnmentioning
confidence: 99%
“…Other studies did not find a similar risk. For example, XRCC1 399Gln was not associated with breast cancer in Chinese (19) and USA women (North Carolina) (20,21), but a protective effect was suggested for Portuguese women with no family history of breast cancer (22). Even though the epidemiological results are not uniform, mechanistic studies indicate that XRCC1 399Gln is detrimental to the cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation